Treatment modalities for advanced ALK-rearranged non-small-cell lung cancer. (April 2016) - Sullivan, Ivana; Planchard, David
The ALK gene plays a key role in the pathogenesis of non-small-cell lung cancer (NSCLC). Patients with NSCLC harboring an ALK -rearrangement represent the second oncogene addiction to be identified in this disease. Crizotinib was the first ALK inhibitor showing pronounced clinical activity, and is now a reference treatment for ALK -positive NSCLC disease. However, despite initial impressive responses to crizotinib, acquired resistance almost invariably develops within 12 months. The pressing need for effective second-line agents has prompted the rapid development of next-generation ALK inhibitors. These agents, notably ceritinib and alectinib as the most developed, have a higher potency against ALK than crizotinib, along with activity against tumors harboring crizotinib-resistant mutations and potentially improved CNS penetration.